Prevalence and Risk Factors of Hepatitis B and C Virus Co-Infection among Women Attending Antiretroviral Therapy Clinic in Yola, Nigeria - Maryam Adam Ibrahim1*; James Hamuel Doughari2 (Journal of Medical Microbiology and Infectious Diseases)
Introduction: Viral hepatitis represents a significant challenge to public health worldwide. Women living with HIV are at heightened risk of coinfection with hepatitis B and C due to their increased risk of exposure to bloodborne pathogens through medical interventions, potentially leading to severe health outcomes, including increased morbidity and mortality, and public health impacts through maternal transmission. This study aimed to estimate the prevalence of hepatitis B and C virus co-infection among women living with HIV attending the ART clinic in Modibbo Adama University Teaching Hospital, Yola, Nigeria. These findings will inform the development and improvement of testing, vaccination, and treatment programs to enhance health outcomes and quality of life for this population. Method: A cross-sectional study was conducted from January 2023 to September 2023 using a convenience sampling method to recruit 360 women aged 18 years and above attending the ART clinic. Data on sociodemographic characteristics and potential risk factors for HBV/HCV infection were collected with a structured questionnaire. The seroprevalence of HBsAg and anti-HCV antibodies was determined with Rapid Diagnostic Test (RDT) strips from Micropoint. Results: Among the 360 HIV-positive women tested, 9.2% (33) were co-infected with HBV, 2.2% (8) were coinfected with HCV, and 0.3% (1) had co-infection with HBV, HCV, and HIV. The prevalence of HBV co-infection was highest among women aged 39-48 (9.6%), while HCV co-infection was most prevalent in those aged 49 and above (3.4%). Logistic regression analysis showed that blood transfusion and having multiple sexual partners were significantly associated with HIV/HBV co-infection (P-value = 0.002). Conclusion: This study identified a notable prevalence of HBV (9.2%) and HCV (2.2%) co-infection among women living with HIV, underscoring the public health significance due to the potential for increased morbidity and mortality. Further studies should employ molecular techniques like PCR to confirm active infections and assess viral loads. This information is crucial for guiding treatment decisions and improving clinical outcomes for this vulnerable population.